IMPLEMENTASI DIGITALISASI SEKOLAH DALAM PEMBELAJARAN DI UPTD SPNF SKB KOTA SALATIGA - Riyanik; Noormiyono (STKIP Subang, 2024)
Education in the era of industrial revolution 4.0 is certainly inseparable from digitalization. The implementation of school digitalization in learning can improve the quality of education. Using a type of field research with a qualitative approach. Meanwhile, the method used is descriptive research method. The results of this research show that the learning process carried out by tutors has used digital-based interactive media, tutors in implementing learning have used digital-based learning media. In implementing the teaching and learning process, adequate infrastructure support is needed. development of human resources, the Salatiga City UPTD SPNF SKB Institute holds In House Training (IHT), or similar training related to the development of the world of digitalization in education. In digital development, quite a small amount of money is required, for the new development process a new IT TEAM is carried out which can be used in developing the learning process.